Effect of emulsified palm oil biodiesel-diesel blends to the combustion characteristics of compression ignition engine - W. N., Maawa; R., Mamat; I. M., Yusri; Febrina, R. (IOP Publishing, 2019)
The increasing energy consumption and the high rate exhaustion of fossilized fuels encourage researchers to find new alternative for the future generation. One of the possible solution to dampen the rate is by biodiesel-water emulsion. In the present study, emulsified biodiesel with 5% (B20W5), 10% (B20W10), 20% (B20W20) and 30% (B20W30) of water in volume were prepared with diesel-biodiesel blend (B20) to be used as fuel in an unmodified compression ignition direct injection engine. All tests were operated at engine speed of 2500 rpm and two different loads namely 20% and 40%. The in-cylinder pressure traces obtained from the series of experiments were used to investigate the trends of rate of heat release (RoHR), rate of pressure rise (RoPR) and mass fraction burned (MFB). The results show that the peak in-cylinder pressure was reduced by 5.9% and the maximum of RoHR is decreased by 8.8%. Furthermore the peak value of RoPR also decrease by 6.4%. All the results were achieved by using B20W5. Therefore, the emulsion of diesel-biodiesel blend is suitable as an alternative technique to improve combustion characteristics while lessen the dependency on fossil fuels.